Development of independent foreign language learning skills among students majoring in psychology and pedagogy - Baetova E.M.; Ashirhanova K.M. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2026)
The topic of enhancing autonomous foreign language acquisition for psychology and pedagogy majors is examined in this article. The study's importance arises from the necessity of fostering learners' independence, self–control, and sustainable language learning capabilities in order to fulfill the demands of contemporary professional education. The study's goal is to pinpoint the pedagogical circumstances, approaches, and resources that support students' successful autonomous learning. The study made use of observation, educational modeling, student questionnaires, and literature analysis. The findings show that using digital educational materials, developing metacognitive methods, and designing personalized learning paths can maximize autonomous learning.
Keywords: digital resources; independent learning; learner autonomy; foreign languages; psychological and pedagogical education; and metacognitive techniques